Adrenergic and Glucocorticoid Receptors in the Pulmonary Health Effects of Air Pollution - Myles X. Hodge; Andres R. Henriquez; Urmila P. Kodavanti (Toxics, 2021)
Adrenergic receptors (ARs) and glucocorticoid receptors (GRs) are activated by circulating catecholamines and glucocorticoids, respectively. These receptors regulate the homeostasis of physiological processes with specificity via multiple receptor subtypes, wide tissue-specific distribution, and interactions with other receptors and signaling processes. Based on their physiological roles, ARs and GRs are widely manipulated therapeutically for chronic diseases. Although these receptors play key roles in inflammatory and cellular homeostatic processes, little research has addressed their involvement in the health effects of air pollution. We have recently demonstrated that ozone, a prototypic air pollutant, mediates pulmonary and systemic effects through the activation of these receptors. A single exposure to ozone induces the sympathetic–adrenal–medullary and hypothalamic–pituitary–adrenal axes, resulting in the release of epinephrine and corticosterone into the circulation. These hormones act as ligands for ARs and GRs. The roles of beta AR (βARs) and GRs in ozone-induced pulmonary injury and inflammation were confirmed in a number of studies using interventional approaches. Accordingly, the activation status of ARs and GRs is critical in mediating the health effects of inhaled irritants. In this paper, we review the cellular distribution and functions of ARs and GRs, their lung-specific localization, and their involvement in ozone-induced health effects, in order to capture attention for future research.